Synthesis, Characterization, and Antimicrobial Activity Studies of Ni(II) Complex with Pyridine as a Ligand - Faridul Islam; Md. Amran Hossain; Nur Mostaq Shah; Hridika Talukder Barua; Md. Alamgir Kabir; Mohammad Jamshed Khan; Romel Mullick (Journal of Chemistry)
We represent a metal complex which has been synthesized by the simple reaction with Ni(II) chloride and pyridine (as a lignd) affording a complex having the molecular formula [NiC5H5N2Cl2], characterized on the basis of elemental analyses, electronic, infrared, 1H NMR, 13C NMR spectra, magnetic susceptibility, and also aid of molar conductivity measurement. Conductivity measurement reveals nonelectrolytic nature of the complex. IR and 13C NMR spectra reveal the presence of cis- and trans-structure. On the basis of above analyses the square planar cis- and trans-structures are proposed for the prepared complex.